„Nomina instrumenti” z sufiksem „-k(а)” w języku rosyjskim - Kuligowska, Katarzyna (Studia Rossica Posnaniensia, 2010)
The purpose of the article is to present the status of the derivational category nomina instrumenti in the light of cognitive linguistics. The adoption of the prototype approach allows to broaden the category nomina instrumenti by the names, which have been often excluded from it. The results of structural and semantic analysis of nomina instrumenti with the suffix -k(a) in the contemporary Russian language have been presented.